Negative body talk measures for Asian, Latina(o), and White women and men: Measurement equivalence and associations with ethnic-racial identity. (June 2018) - Sladek, Michael R.; Salk, Rachel H.; Engeln, Renee
Highlights: Negative body talk (NBT) measures have been developed with mostly White samples. Two measures were equivalent for Asian, Latina(o), and White university students. Ethnic group comparisons showed few differences with small effect sizes. Women's ethnic-racial identity linked with less frequent NBT. Men's ethnic-racial identity linked with more frequent NBT. Abstract: Negative body talk measures have been developed with predominantly White, female samples. We tested measurement invariance (equivalence) of two available negative body talk scales for Asian, Latina(o), and White college women and men in the U.S. In Study 1 ( n  = 1501 women; n  = 1436 men), multiple group confirmatory factor analyses indicated scalar (strong) invariance across groups for the Negative Body Talk (Engeln-Maddox, Salk, & Miller, 2012) and Male Body Talk (Sladek, Engeln, & Miller, 2014) scales, suggesting these measures can be used to test mean group differences. Ethnic group comparisons adjusting for body mass index (BMI) showed similarities overall; few differences that emerged had small effect sizes. In Study 2 ( n  = 227 women; n  = 141 men), greater ethnic-racial identity resolution was associated with less frequent negative body talk for Latina and Asian women but more frequent muscularity-focused negative body talk for Asian men, adjusting for BMI.